Approaches and outcomes of adalimumab discontinuation in patients with well-controlled inflammatory arthritis: a systematic search and review - Erin Balay-Dustrude; Jessica Fennell; Kevin Baszis; Y. Ingrid Goh; Daniel B. Horton; Tzielan Lee; Chloe Rotman; Anna Sutton; Marinka Twilt; Olha Halyabar; for the CARRA JIA Inactive Disease Workgroup (Pediatric Rheumatology Online Journal)
Abstract Objective This systematic search and review aimed to evaluate the available literature on discontinuation of adalimumab and other tumor necrosis factor inhibitors (TNFi) for patients with well-controlled chronic inflammatory arthritides. Methods We conducted a publication search on adalimumab discontinuation from 2000–2023 using PubMed, CINAHL, EMBASE, and Cochrane Library. Included studies evaluated adalimumab discontinuation approaches, tapering schemes, and outcomes including successful discontinuation and recapture after flare, in patients with well-controlled disease. Studies included evaluated rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, and juvenile idiopathic arthritis (JIA). Results Forty-nine studies were included. Studies evaluating adalimumab alone were limited, and many reported TNFi outcomes as a single entity. Studies on rheumatoid arthritis (RA) (32, 8 RCTs) reported flare rates from 33–87%. Flares with medication tapering were slightly lower than with abrupt stop, and successful recapture was generally high (80–100%). Studies on spondyloarthropathy (12, 4 RCTs), focused on tapering, noting lower flare rates in tapering rather than abruptly stopping, and high recapture rates (~ 90%). Studies on JIA (5) were observational and demonstrated modestly lower flare rates with tapering (17–63%) versus abrupt stopping (28–82%). There was notable variability in study design, follow-up duration, specificity for TNFi results, and controlled pediatric studies. Conclusion The literature evaluating adalimumab and other TNFi discontinuation, flare rates, and recapture success within the inflammatory arthritis population demonstrated less flare when medications were tapered, over abrupt stop in the RA, spondyloarthropathy, and JIA populations. When medications were restarted after flare, recapture of well-controlled disease was generally high in RA and spondyloarthropathy, and generally favorable in JIA.